Design and construction of an improved production line counter - Adekanmbi, Martins; Ogotute, Anthony Awajisenyinayenmi; Amaechi, Chukwuwendu Jeffrey (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
A production line is a type of production system where products or products go through several workstations in a fixed or predetermined sequential order. In this work, a production line counter was designed, and also applies CAD approach to ensure minimal errors during construction. This device consists of an ESP32 development board which serves as the microcontroller in this design, an SD-Card module for offline data storage, a Real Time Clock (RTC) for accurate recording of time and date and a 5V power supply. The counting of objects or products in this work is restricted to unidirectional counting. This is to be achieved using an IR sensor consisting of an IR emitter and an IR receiver. As objects pass by this sensor, IR waves from the IR emitter which emits infrared waves are reflected and received by the IR receiver which results in a HIGH output signal from the IR sensor. This HIGH signal is received by the microcontroller and increments the counter value by 1. The counter value is updated on the SD Card and on the IP address of the ESP32 which serves as the webserver. This counter value can thus be accessed via a web browser by the Wi-Fi of the ESP32 thus, enabling offline and online access to data and also providing an automated means of storing and retrieving data of the production process.